Clinical Practice Variation in the Management of Staphylococcus aureus Bacteremia: Results from an Emerging Infections Network Survey. (4th October 2017) - Strnad, Luke; Beekmann, Susan E; Polgreen, Philip M; Chambers, Henry; Liu, Catherine
Abstract: Background: Infectious disease (ID) consultation for Staphylococcus aureus bacteremia (SAB) has been associated with significant improvement in patient outcomes and mortality. However, as highlighted by recent posts on the Emerging Infections Network (EIN) listserv, there exists substantial practice variation among ID providers in the management of certain aspects of this condition. To assess provider opinion and practice habits in the management of SAB, we developed a vignette based survey administered through the EIN. Methods: We developed an 11 question survey using clinical vignettes targeting areas in the management of SAB where data are limited or controversial. The survey was developed by the study authors with β-testing by fellows and faculty at three academic institutions. The web-based survey was open between January 5, 2017 and January 30, 2017. Data analysis was performed by the study authors. Results: Of 1, 286 EIN physician members with an adult ID practice, 723 (56%) responded to this survey. Respondents were significantly more likely than non-respondents to have ≥ 25 years of post-fellowship practice ( P < 0.0001). Areas where there was consensus in management by 3 two-thirds of respondents included: Treatment of SAB due to a skin and soft tissue source with 2 weeks of intravenous antibiotics and treatment of a single positive blood culture for S. aureus as a true pathogen in the absence of other systemic symptoms rather than discounting as a contaminant. Although 71% of respondents would perform transthoracic echocardiogram on every patient with SAB, there was significant variation in the use of transesophageal echocardiogram (Figure 1). Heterogenous practice patterns were identified in management of vancomycin MIC of 2, persistent bacteremia, daptomycin dosing, deep venous thrombosis, routine diagnostic evaluation of SAB, and in other areas (Figures 2 and 3). Conclusion: In a large survey of adult ID providers, there is considerable practice variation in the management of SAB. This is particularly true for areas where literature is minimal or inconclusive, but is even present in areas where there is expert consensus. These findings highlight directions for future research and help to inform target areas for guideline development on SAB. Disclosures: H. Chambers, AstraZeneca: Board Member, Consulting fee; Cubist: Grant Investigator and Scientific Advisor, Consulting fee and Grant recipient; Merck: Shareholder, stock income